DARI PERANTAIAN HINGGA KERJA PAKSA: PEMBANGUNAN POELAOE BOEI DAN EKSPLOITASI ORANG BUANGAN DI NUSAKAMBANGAN 1861-1935 - , Samingan; , Dr. Sri Margana, M. Phil, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study explored the changes in colonial policy on security, prison and the use of convicts at Nusakambangan in the late colonial period. The topic was raised because of the lack of historical study of the prison and its administration in the island. It used historical method with primary source of archives and secondary source of articles, books, magazines, journals, and others. The main subject of this study was the colonial interest in establishing special prison (poelaoe boei) and the main questions of the study are why colonial government required special prison in Nusakambangan Island and how the colonial government used the convicts for its politic and economic interests. The important findings of the study were: 1) The important geographic position and economic potentials of the island became the consideration of the establishment of the prison